The Association Between Payer Source and Traumatic Brain Injury Rehabilitation Outcomes: A TBI Model Systems Study. Issue 1 (21st January 2023) - Lequerica, Anthony H.; Sander, Angelle M.; Pappadis, Monique R.; Ketchum, Jessica M.; Jaross, Marissa; Kolakowsky-Hayner, Stephanie; Rabinowitz, Amanda; Callender, Librada; Smith, Michelle
Abstract : Objective: To examine the relationship between payer source for acute rehabilitation, residential median household income (MHI), and outcomes at rehabilitation discharge after traumatic brain injury (TBI). Setting: Acute inpatient rehabilitation facilities. Participants: In total, 8558 individuals enrolled in the Traumatic Brain Injury Model Systems (TBIMS) National Database who were admitted to inpatient rehabilitation between 2006 and 2019 and were younger than 64 years. Design: Secondary data analysis from a multicenter longitudinal cohort study. Main Measures: Payer source was divided into 4 categories: uninsured, public insurance, private insurance, and workers' compensation/auto. Relationships between payer source with residential MHI, rehabilitation length of stay (RLOS), and the FIM Instrument at discharge were examined. Covariates included age, injury severity, FIM at admission, and a number of sociodemographic characteristics including minority status, preinjury limitations, education level, and employment status. Results: Individuals with workers' compensation/auto or private insurance had longer RLOS than uninsured individuals or those with public insurance after controlling for demographics and injury characteristics. An adjusted model controlling for demographics and injury characteristics showed a significant main effect of payer source on FIM scores at discharge, with the highest scores noted among those with workers' compensation/auto insurance. The main effect of payer source on FIM at discharge became nonsignificant after RLOS was added to the model as a covariate, suggesting a mediating effect of RLOS. Conclusion: Payer source was associated with preinjury residential MHI and predicted RLOS. While prior studies have demonstrated the effect of payer source on long-term outcomes due to lack of inpatient rehabilitation or quality follow-up care, this study demonstrated that individuals with TBI who are uninsured or have public insurance may be at risk for poorer functional status at the point of rehabilitation discharge than those with private insurance, particularly compared with those with workers' compensation/auto insurance. This effect may be largely driven by having a shorter length of stay in acute rehabilitation.